2019
DOI: 10.1002/ppsc.201900003
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Chiral Ag4Pd2(SR)8 by Nonreplaced Galvanic Reaction

Abstract: Galvanic reaction is a classic reaction and widely applied in nanoscience and nanotechnology. However, it is rarely employed in the synthesis of doped metal nanoclusters with size less than ≈2 nm and remains to be exploited in nanocluster (NC) community. Herein, it is reported the synthesis of chiral Ag4Pd2(SR)8 starting from Ag25(SR)18 NC via a galvanic reaction and the characterization of the as‐obtained NC by multiple techniques such as single crystal X‐ray crystallography and X‐ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…[178,181] Zhu and co-workerss ynthesized [Ag 4 Ni 2 (2,4-SPhMe 2 ) 8 ] 0 in 2018. [179] In 2019, Wu et al [180] [179][180][181] Each type of NC has a geometrical structure in which eight SR are coordinated to an octahedral Ag 4 M 2 core at two points. Such as tructure is similar to that of [Au 4 M 2 (SR) 8 ] 0 (M = Pt or Pd) described in Section3 .1.…”
Section: [Au 25àmentioning
confidence: 99%
See 1 more Smart Citation
“…[178,181] Zhu and co-workerss ynthesized [Ag 4 Ni 2 (2,4-SPhMe 2 ) 8 ] 0 in 2018. [179] In 2019, Wu et al [180] [179][180][181] Each type of NC has a geometrical structure in which eight SR are coordinated to an octahedral Ag 4 M 2 core at two points. Such as tructure is similar to that of [Au 4 M 2 (SR) 8 ] 0 (M = Pt or Pd) described in Section3 .1.…”
Section: [Au 25àmentioning
confidence: 99%
“…[Ag 4 Pd 2 (2,4-SPhMe 2 ) 8 ] 0 has an enantiomer similar to that of [Au 4 M 2 (PET) 8 ] 0 (M = Pt or Pd) (Figure 29 D). [180] Figure 30 As hows the optical absorption spectra of [Ag 4 M 2 (DMSA) 4 ] 0 (M = Pt, Pd, or Ni). [181] As the substitution element changed from Ni to Pd to Pt, the main peak in the absorptions pectra blue shifted.…”
Section: Ag Nàmentioning
confidence: 99%
“…[47] X-ray photoelectron spectroscopy (XPS) studies further confirmed the synergetic interaction of Ag and Au within Ag 2 Au 50 -(PET) 36 .Itis observed from Figure S17 that the Au 4f binding energies of Ag 2 Au 50 (PET) 36 were positively shifted compared to those of Au 25 (PET) 18 ,and the Ag 3d binding energies were negatively shifted compared to those of AgÀSR complex. [48] This definitely indicates the electron transfer between Au and Ag of Ag 2 Au 50 (PET) 36 ,which is further evidenced by HOMO and LUMO predictions ( Figure S13 18 , either bonded to as taple-Auw ith E ads = À0.26 eV and n CO = 2027 cm À1 ,o rt othree staple-Auw ith E ads = À0.21 eV and n CO = 2072 cm À1 ( Figure S18 and Table S4). ForA g 2 Au 50 -(SR) 36 ,C Oc an additionally adsorb at the Ag + sites and the CÀOv ibrational stretching frequency (n CO )f or the linear Ag + ÀCO adsorption is predicted to be 1997 cm À1 ,i nr easonable agreement with the experiment (Figure S16a and Table S4).…”
Section: Angewandte Chemiementioning
confidence: 75%
“…The reactions between metal cations and the parent metal NCs can be accomplished by a conventional galvanic reaction. 157 These results highlight the decisive role of metal cations in the reaction with metal NCs.…”
Section: Molecular Interactions/reactions In Alloying Of Metal Ncsmentioning
confidence: 88%